Concept of world cities: human-geographical approach - Husieva, N. V.; Kucheriava, G. O.; Suptelo, O. S. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The phenomenon of world (global) cities is of considerable interest and is the subject of research of specialists from different spheres. The study of world cities at the present stage of the society’s development is complicated by a number of aspects, including complex and dynamic development of the geopolitical and geoeconomic world space, which explains rapid transformation of cities; the complexity of a statistical base formation for the study of world cities, expressed in a large amount of diverse information and limited access to it; lack of a holistic and unique methodology for studying world cities.The purpose of the article. The article studies the human-geographical approach to the formation and development of the concept of world (global) cities in the XX‒XXI centuries.Results. In modern scientific literature there are a number of terms describing the phenomenon of world cities, in particular, including «global city», «world center», «world financial center», «сosmopolis», «information city», «media city», «metropolis», «ecumenopolis», «global city region», «сapitals of capital», «international city», «globalizing city» «megacity», «interactive city», etc. The variety of terms is an indicator that reflects the ambiguity and complexity of this phenomenon in modern science, as well as the diversity of approaches to its study. Definition of «world cities» concept is based on such aspects as economic development, political influence, social significance.Formation of the world cities concept has a fairly long history. A significant contribution to its formation and development was made by P. Geddes, P. Hall, C. Doxiadis, F. Braudel, H. Reed, J. Friedmann, G. Wolff, N. Thrift, S. Sassen, M. Castells, C. Abbott, Y. Jao, A. E. Tschoegl, Y. Cassis, P. Taylor, A. Scott, P. Marcuse, R. Van Kempen, E. Isin, D. Clark, N. A. Slucka, S. McQuayer and others. In their research, the world city is, firstly, as a phenomenon unique and singular; secondly, the scope of its influence clearly has a planetary or, ultimately, macro-regional coverage; thirdly, the world city represents a special force concentrator, whether in the field of ideology, religion, military force, innovation economy, etc.; fourthly, it acts as a hegemon, functions as a governing and controlling element within the framework of another, «subordinate» territorial-social system; fifthly, the spatial organization of such a system has a clearly pronounced center-peripheral character; sixthly, the presence of the dominant one-, two-way links that support the system.Several approaches to identifying the phenomenon of a world city based on different principles can be singled out: geoeconomic, geopolitical, socio-cultural, historical-geographic, geodemographic, information and communication, service, innovation. Human-geographical approach is important as it combines all of the above-mentioned and provides the most comprehensive study of the phenomenon of world cities.